UJI LIMBAH KULIT BUAH NANAS (Ananas comosus L. Merr) DAN PUPUK KANDANG KAMBING SEBAGAI PUPUK ORGANIK CAIR PADA TANAH SALIN (Studi Kasus di Baratajaya, Kecamatan Gubeng, Kota Surabaya) - Detta Anugrah Heni; Kemal Wijaya; Purnomo Edi Sasongko (Agros Journal of Agriculture Science, 2023)
An increase in the amount of land in Indonesia submerged by sea water will cause an increase in the amount of salt-stressed land (saline land), one of the disturbances is the absorption of nutrients. Pineapple peel waste (Ananas comosus L. Merr) found in Surabaya has not been used properly by the community. The purpose of the research was to determine the superiority of pineapple peel waste to be used as liquid organic fertilizer. The method used is the experimental design method, after the manufacture of liquid organic fertilizer is complete, followed by testing the nutrient content there are 4 types of parameters, namely pH meter, EC meter, nitrogen (N), total phosphorus (P2O5) and potassium oxide (K2O). This research was carried out in the front yard of the house, testing and calibration laboratory. This study used a factorial Completely Randomized Design (CRD), the factors tested were pineapple peel waste and goat manure consisting of 5 treatments. Each treatment was repeated 4 times to obtain 20 experimental polybags. Factorial (mass of pineapple peel waste and goat manure) for each treatment mass (1 : 1): NK0 formula without pineapple peel waste and goat manure, NK1 formula + pineapple peel waste and goat manure 250 g/ml (1 : 1), NK2 formula + pineapple peel waste and goat manure 500 g/ml (1 : 1), NK3 formula + pineapple peel waste and goat manure 750 g/ml (1 : 1), NK4 formula + pineapple peel waste and goat manure 1000 g/ml (1 : 1). Notes : N Pineapple peel waste (Ananas comosus L. Merr) ; K Goat manure. The data obtained were analyzed by Sidik Variety analysis (ANOVA). If the results of the study show a significant effect, it will be continued with the Honest Significant Difference (BNJ) test at the 5% level. The data obtained were analyzed by Sidik Variety analysis (ANOVA). If the results of the study show a significant effect, it will be continued with the Honest Significant Difference (BNJ) test at the 5% level.INTISARIPeningkatan jumlah daratan di Indonesia yang terendam air laut akan menyebabkan jumlah lahan tercekam garam (lahan salin) meningkat, salah satu gangguan adalah penyerapan unsur hara. Limbah kulit buah nanas (Ananas comosus L. Merr)  yang terdapat di Surabaya belum dimanfaatkan dengan baik oleh masyarakat. Tujuan penelitian yang dilakukan  adalah untuk mengetahui keunggulan limbah kulit buah nanas untuk dimanfaatkan sebagai pupuk organik cair. Metode yang digunakan adalah metode desain eksperimen, setelah pembuatan pupuk organik cair selesai, dilanjutkan pengujian kandungan unsur hara terdapat 4 jenis parameter yaitu pH meter, EC meter, nitrogen (N), phospor total (P2O5) dan kalium Oksida (K2O). Penelitian ini dilaksanakan di pekarangan depan rumah, laboratorium pengujian dan kalibrasi. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) faktorial, faktor yang diujikan adalah limbah kulit buah nanas dan pupuk kandang kambing terdiri atas 5 perlakuan. Setiap perlakuan diulang sebanyak 4 kali sehingga memperoleh 20 polybag percobaan. Faktorial (Massa limbah kulit buah nanas dan pupuk kandang kambing) masing-masing massa perlakuan (1 : 1) : NK0 formula tanpa limbah kulit buah nanas dan pupuk kandang kambing, NK1 formula + limbah kulit buah nanas dan pupuk kandang kambing 250 g/ml (1 : 1), NK2 formula + limbah kulit buah nanas dan pupuk kandang kambing 500 g/ml (1 : 1), NK3 formula + limbah kulit buah nanas dan pupuk kandang kambing 750 g/ml (1 : 1), NK4 formula + limbah kulit buah nanas dan pupuk kandang kambing 1000 g/ml (1 : 1). Keterangan : N Limbah kulit buah nanas (Ananas comosus L. Merr) ; K Pupuk kandang kambing. Data yang diperoleh dianalisis dengan analisis Sidik Ragam (ANOVA). Apabila hasil penelitian menunjukkan pengaruh nyata dilanjutkan dengan uji Beda Nyata  Jujur (BNJ) pada taraf 5%